Ipteks bagi Masyarakat (IbM) Kelompok Nelayan Purse Seine Di Desa Siddo Kecamatan Soppengriaja Kabupaten Barru - Malik, Andi Adam (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2018)
The partner's problem is the high cost of fuel If the fishing area around Siddo usually spends 50 ? 100 liters pertrip (Rp250.000 ? Rp 500.000). If the fishing area is very far away, then the number of operating days is usually 3 to 4 dayslater it takes 300 - 400 liters per trip (Rp1,500,000 - Rp2,000,000). The catching area was unclear, and the catch in 2009 hasdecreased, one of the problems is allegedly caused by fishermen not using the latest fishing technology, including the useof fishing aids (global position system, fish finder). How to get potential fishing locations and at the same time read fishingmaps, resulted in the search for an extensive fishing area and certainly needed a lot of fuel. The purpose of this activity isto 1). Increase catches and reduces operational costs 2). Improve the ability of purse seine fishersto use fishing aids andable to independently read fishing maps. The benefits of this activity are expected to increase fishermen's income. Themethod used is Participatory Rural Appraisal (PRA) And implementation methods namely counseling, training anddemonstration and evaluation. Apply fishing aids according to maps of fishing grounds issued by the Indonesian Ministryof Maritime Affairs and Fisheries. The results of this activity are very satisfying. Fisherman's mindset to use training onhow to calculate ice usage has added the ability to calculate ice usage according to the number of fish to be preservedMentoring fishers in the practice of using fishing aids and developing business partners as well as how to read a fishingmap excellent response. Finally able to use and interested in buying a similar tool. The conclusion of the activity is 1)Fishing aids have affected the catch and reduced operational costs, 2) Fishermen have been able to read fishing maps theninput into GPS independently